2019
DOI: 10.1080/2162402x.2019.1574197
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone marrow SUVmax on 18F-FDG PET is associated with higher pelvic treatment failure in patients with cervical cancer treated by chemoradiotherapy and brachytherapy

Abstract: The aim of this study was to evaluate if bone marrow (BM) SUVmax measured on pre-treatment 18F-FDG PET/CT predicts the clinical outcome of locally advanced cervical cancer (LACC). We recruited retrospectively patients with LACC who underwent staging 18F-FDG PET/CT and had baseline blood tests, then treated by chemoradiation therapy (CRT), followed by image-guided adaptive brachytherapy (IGABT). BM SUVmax was calculated and correlated to inflammatory blood markers. Tumor size and pelvic lymph node involvement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In the area of gynecological cancer, 2 previous studies have investigated the prognostic significance of BM FDG-uptake 23 , 24 : both studies included patients with cervical cancer and their conclusions were similar to ours, but performed no mechanistic investigations. For ovarian and endometrial cancer, our study is the first investigate the prognostic significance of BM FDG uptake.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the area of gynecological cancer, 2 previous studies have investigated the prognostic significance of BM FDG-uptake 23 , 24 : both studies included patients with cervical cancer and their conclusions were similar to ours, but performed no mechanistic investigations. For ovarian and endometrial cancer, our study is the first investigate the prognostic significance of BM FDG uptake.…”
Section: Discussionsupporting
confidence: 56%
“…The reason for this, as well as whether this finding is universal, remains unknown. However, previous investigations have suggested that pretreatment neutrophilia as well as the greater tumor G-CSF expression are more frequently observed in advanced-stage disease than in early-stage disease in endometrial or ovarian cancer patients [22][23][24][25] . These results may indicate that the amount of tumor-derived G-CSF is greater in advanced-stage disease than in early-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic tumor volume (MTV) and glucose metabolism of normal tissues associated with immunity on 18 F-FDG PET/CT before and during immune checkpoint inhibitor (ICI) therapy have been explored as predictors of therapeutic efficacy (1)(2)(3)(4). The link between 18 F-FDG uptake by immunemediating tissues, such as the bone marrow (BM) and spleen, and poor cancer outcomes is hypothesized to be explained by generalized (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the PD-L1 expression, easily measurable and accessible biomarkers for the prediction of outcomes are needed. Initial investigations, including a complete blood count and a 18F-Fluorodeoxyglucose positron emission tomography (FDG-PET), provide both diagnostic and staging information [ 9 , 10 , 11 ], but could also be predictive or prognostic [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. On the basis of these two tests, certain parameters are beneficial and meaningful, particularly the derived neutrophils to lymphocytes ratio (dNLR) and the total metabolic tumor volume (TMTV) on FDG-PET [ 19 ].…”
Section: Introductionmentioning
confidence: 99%